Development of “BANTING” Learning Media for Vocational High School Students: Pengembangan Media Pembelajaran “BANTING” untuk Siswa Sekolah Menengah Kejuruan - Dini Nurul Hidayah; Fitria Nur Hasanah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to produce teaching material products in the form of digital book learning media or E-Books used in the Network System Administration subject for class XI SMK Muhammadiyah 1 Taman and test the feasibility. The development research method used in the E-Book learning media research is R&D (Research and Development) and to develop the E-Book research design it refers to the ADDIE development model which consists of the analysis (analysis), design (design), development (development) stages. , implementation (implementation) and evaluation (evaluation). The subjects of this research are students of class XI majoring in Computer and Network Engineering using a research instrument in the form of a questionnaire. The data obtained will then be analyzed using the likert scale. After the development process, media expert validation and material expert validation were carried out. The results of media expert validation got a score of 87.8% in the Very Good category, the results of material expert validation got a score of 86.6% in the Very Good category, and student responses got a score of 96.44% in the Very Good category. So it can be concluded that the BANTING learning media is very good for use in learning. Highlights: The study focuses on developing E-Book learning media for Network System Administration in a specific school, SMK Muhammadiyah 1 Taman. The research follows the R&D approach and utilizes the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The research involves students of class XI majoring in Computer and Network Engineering as the subjects, using a questionnaire as a research instrument and analyzing the data using the likert scale. Keywords: E-Book learning media, Network System Administration, Feasibility, R&D (Research and Development), ADDIE development model.